Kerjasama Ekonomi Korea Selatan dan Indonesia di Masa Kini dan Masa Depan - Jeong, Young Kyu (UI Scholars Hub, 2003)
This study analyzes the changes and characteristics of economic cooperation between Korea and Indonesia during the period from 1980 to 2002. Gross trade and direct investments are studies here, as well as ODA such as per categorries, field, in order to understand Korea- Indonesia's economic cooperation. Crude oil, gas and other natural resources took up the greatest portion of Indonesia exports until the 2002, Since the mid-1980's, exports have grown by a large margin owing to the nation's export-oriented economic development strategy and stabilization of oil prices. Trade and direct investment showed a continuous increase throughout the period, with the exception of a temporary decrease in 1997 economic crisis. The result of trade, investment and ODA shows that Indonesia and Korea very important country for economic growth.